Crystallographic analysis of new psychrophilic haloalkane dehalogenases: DpcA from Psychrobacter cryohalolentis K5 and DmxA from Marinobacter sp. ELB17 - Tratsiak, Katsiaryna; Degtjarik, Oksana; Drienovska, Ivana; Chrast, Lukas; Rezacova, Pavlina; Kuty, Michal; Chaloupkova, Radka; Damborsky, Jiri; Kuta Smatanova, Ivana (Acta crystallographica. Section F, Structural biology and crystallization communications, 2013)
Haloalkane dehalogenases are hydrolytic enzymes with a broad range of potential practical applications such as biodegradation, biosensing, biocatalysis and cellular imaging. Two newly isolated psychrophilic haloalkane dehalogenases exhibiting interesting catalytic properties, DpcA from Psychrobacter cryohalolentis K5 and DmxA from Marinobacter sp. ELB17, were purified and used for crystallization experiments. After the optimization of crystallization conditions, crystals of diffraction quality were obtained. Diffraction data sets were collected for native enzymes and complexes with selected ligands such as 1-bromohexane and 1,2-dichloroethane to resolutions ranging from 1.05 to 2.49 Å.
Keywords: Catalytic Domain; bakteriální proteiny; Crystallography, X-Ray; Marinobacter; Psychrobacter; krystalografie rentgenová; X-Ray Diffraction; Hydrolases; DpcA; Marinobacter sp. ELB17; Psychrobacter cryohalolentis K5; haloalkane dehalogenases; difrakce rentgenového záření; Bacterial Proteins; katalytická doména; DmxA; hydrolasy